Pattern of ECG abnormality in Type 2 diabetic patients in Shendi locality- Sudan - MA, Eltigani; Abbas, Asia; Ishag, Masud (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
In type 2 diabetes mellitus ECG abnormalities are almost the rule.This study was conducted to know the impact of ECG abnormality on lipid profilein type 2 diabetic patients.